HYDROGEN ISOTOPE GEOCHEMISTRY OF CHROMITE-BEARING ULTRAMAFIC ROCKS OF THE URALS - Bryanchaninova N.I.; Makeyev A.B.; Dubinina E.O. (My University, 2004)
The source of water responsible for serpentinite formation is one of the oldest problems in geology. Some data on the isotopic composition of such metamorphic water can be obtained from the isotopic composition of the metamorphic rocks and their minerals. Accessible outcrops of chromite-bearing ultramafic rocks of the Polar Urals are nearly universally serpentinized. In addition to petrographic investigations, secondary minerals were studied by the thermogravimetric method, which allows determination of hydroxyl-bearing minerals (brucite (Brc), α-β-lizardite (Liz), antigorite (Ant), chrysotile (Hzl , chlorite (Chl), tremolite (Trm), actinolite (Act), antophyllite (Aph), and talc (Tlc)) accurate to 0.1-0.5% [1, 4]. We analyzed more than 2500 samples of serpentinized lherzolites, harzburgites, dunites, olivine-antigorite rocks, and other serpentinites of the Polar Urals (Syumkeu, Raiiz, and Voikar-Syn'in massifs) and southern Urals (Kempirsai Massif). The magnetite (Mgt) and magnesite (Mzt) contents were calculated from magnetic susceptibility data and CO2 content, respectively. Rocks with a low degree of serpentinization (ΣSpn < 20%) or nearly completely serpentinized rocks (ΣSpn > 80%) account for no more than 5% of ultramafic rocks. The average degree of serpentinization of rock massifs in the Polar Urals is 50-60%.